2018
DOI: 10.3390/met8100839
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization of the Primary Stability of Acetabular Press-Fit Cups with Open-Porous Load-Bearing Structures on the Surface Layer

Abstract: Background: Nowadays, hip cups are being used in a wide range of design versions and in an increasing number of units. Their development is progressing steadily. In contrast to conventional methods of manufacturing acetabular cups, additive methods play an increasingly central role in the development progress. Method: A series of eight modified cups were developed on the basis of a standard press-fit cup with a pole flattening and in a reduced version. The surface structures consist of repetitive open-pore loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Murr [164] reported a Ti-6Al-4 V porous acetabular cup, manufactured with the EBM technique ( Figure 8). Weiβmann et al [165] manufactured titanium alloy porous acetabular cups with the SLM technique. They tested three types of cells: twisted, combined and combined open, and found that their mechanical strength depends on the geometry of the unit cell employed, its dimensions and the volume and porosity responsible for the press fit of the prosthesis.…”
Section: Lower Limb Prosthesesmentioning
confidence: 99%
“…Murr [164] reported a Ti-6Al-4 V porous acetabular cup, manufactured with the EBM technique ( Figure 8). Weiβmann et al [165] manufactured titanium alloy porous acetabular cups with the SLM technique. They tested three types of cells: twisted, combined and combined open, and found that their mechanical strength depends on the geometry of the unit cell employed, its dimensions and the volume and porosity responsible for the press fit of the prosthesis.…”
Section: Lower Limb Prosthesesmentioning
confidence: 99%
“…Its reduction will have a positive influence on the reduction of the object's costs, including auxiliary timing and material losses during post-processing (marked in purple in Figure 1). It should be noted that there are several known ways to improve the quality of the parts produced by selective laser melting based on the results of experimental investigations [31][32][33][34][35]:…”
Section: Introductionmentioning
confidence: 99%
“…-An initial analysis of the control factors related to SLM machines on the prepared powders before production with the purpose of receiving confirmed experimental data of the current conditions of the materials and environment; -Improved techniques for pre-treatment of the powders: mechanical pre-treatment with the purpose of obtaining more regular shapes and sizes in the initial powder; thermal pre-treatment It should be noted that there are several known ways to improve the quality of the parts produced by selective laser melting based on the results of experimental investigations [31][32][33][34][35]:…”
Section: Introductionmentioning
confidence: 99%
“…The measurements were taken at 0, 50, 100, 200, 400, 600, 800, and 1000 cycles using a frame rate of 15Hz. For each set of load cycles, we used the optical readings from the cup rim and augment marker points, respectively, to calculate best-fit circles by utilizing the Best Fit Algorithm that then enabled us to measure the maximal and minimal circle diameters at each set of load cycles (see Figure 2) [22,23].…”
Section: Scenario 2: Revision Cup With Large Bony Defect Treated Usinmentioning
confidence: 99%
“…2) [22,23]. We considered elastic deformation to be the change in diameter of these "best-fit" circles from the circle diameter measured initially after implantation without load, which was calculated from the positional changes of the rim markers.…”
Section: Scenario 2: Revision Cup With Large Bony Defect Treated Usinmentioning
confidence: 99%